Impaired left ventricular energy metabolism in patients with hypertrophic cardiomyopathy is related to the extension of fibrosis at delayed gadolinium-enhanced magnetic resonance imaging. Issue 3 (15th August 2008) - Esposito, A; De Cobelli, F; Perseghin, G; Pieroni, M; Belloni, E; Mellone, R; Canu, T; Gentinetta, F; Scifo, P; Chimenti, C; Frustaci, A; Luzi, L; et al.
Abstract : Objective: Areas of intramyocardial late enhancement (LE) at delayed enhanced magnetic resonance imaging (DE-MRI) and reduction of myocardial phosphocreatine (PCr)/ATP-ratio at phosphorus magnetic resonance spectroscopy ( 31 P-MRS) are both reported in hypertrophic cardiomyopathy (HCM) and indicate areas of increased interstitial myocardial space with fibrosis and impairment of myocardial energy metabolism, respectively. We sought to ascertain whether in HCM patients the abnormal features of left ventricular (LV) interstitial space revealed by DE-MRI correlated with impaired LV energy metabolism shown at 31 P-MRS. Methods: 19 patients with HCM proved by histological analysis of multiple endomyocardial biopsies and with normal coronary arteries, underwent cardiac MRI including DE-MRI and 31 P-MRS. DE-MRI for detection and quantification of late enhancement (LE) and 31 P-MRS to assess the myocardial PCr/ATP-ratio were performed by means of a 1.5-T magnet. 19 healthy subjects, matched for gender and age were studied by 31 P-MRS as control group. Results: LE areas in the LV wall were found in 17 out of 19 patients with an extension ranging from 0.8% to 19.5% of the LV-mass (mean value 7.6% (SD 5.6%). The PCr/ATP-ratio was lower in HCM patients than in control subjects (2.18 (0.41) vs 2.41 (0.30); p<0.05). LE% and PCr/ATP-ratio were inversely related (R = −0.57; p<0.05) and LE% was the stronger predictor of PCr/ATP-ratio by multivariate analysis. Conclusions: This study demonstrated that the known alteration of the PCr/ATP-ratio observed in HCM patients is correlated with the presence of fibrotic areas in the myocardium of the left ventricle.